Answer:
slope = 3
point (2, 5)
b = y - m*x
b = 5 -3*2
b = -1
Then we enter the slope and the value of b into this equation:
y = mx + b
y = 3x -1
Source: https://www.1728.org/distance.htm
Step-by-step explanation:
Because u would have to find the undercorse of 010-1 witch makes the out of part by 6
Answer:
The first three nonzero terms in the Maclaurin series is
![\mathbf{ 5e^{-x^2} cos (4x) }= \mathbf{ 5 ( 1 -9x^2 + \dfrac{115}{6}x^4+ ...) }](https://tex.z-dn.net/?f=%5Cmathbf%7B%205e%5E%7B-x%5E2%7D%20cos%20%284x%29%20%20%7D%3D%20%5Cmathbf%7B%205%20%28%201%20-9x%5E2%20%2B%20%5Cdfrac%7B115%7D%7B6%7Dx%5E4%2B%20...%29%20%7D)
Step-by-step explanation:
GIven that:
![f(x) = 5e^{-x^2} cos (4x)](https://tex.z-dn.net/?f=f%28x%29%20%3D%205e%5E%7B-x%5E2%7D%20cos%20%284x%29)
The Maclaurin series of cos x can be expressed as :
![\mathtt{cos \ x = \sum \limits ^{\infty}_{n =0} (-1)^n \dfrac{x^{2n}}{2!} = 1 - \dfrac{x^2}{2!}+\dfrac{x^4}{4!}-\dfrac{x^6}{6!}+... \ \ \ (1)}](https://tex.z-dn.net/?f=%5Cmathtt%7Bcos%20%5C%20x%20%3D%20%5Csum%20%5Climits%20%5E%7B%5Cinfty%7D_%7Bn%20%3D0%7D%20%28-1%29%5En%20%5Cdfrac%7Bx%5E%7B2n%7D%7D%7B2%21%7D%20%3D%201%20-%20%5Cdfrac%7Bx%5E2%7D%7B2%21%7D%2B%5Cdfrac%7Bx%5E4%7D%7B4%21%7D-%5Cdfrac%7Bx%5E6%7D%7B6%21%7D%2B...%20%20%5C%20%5C%20%5C%20%281%29%7D)
![\mathtt{e^{-2^x} = \sum \limits^{\infty}_{n=0} \ \dfrac{(-x^2)^n}{n!} = \sum \limits ^{\infty}_{n=0} (-1)^n \ \dfrac{x^{2n} }{x!} = 1 -x^2+ \dfrac{x^4}{2!} -\dfrac{x^6}{3!}+... \ \ \ (2)}](https://tex.z-dn.net/?f=%5Cmathtt%7Be%5E%7B-2%5Ex%7D%20%3D%20%5Csum%20%5Climits%5E%7B%5Cinfty%7D_%7Bn%3D0%7D%20%20%5C%20%5Cdfrac%7B%28-x%5E2%29%5En%7D%7Bn%21%7D%20%3D%20%5Csum%20%5Climits%20%5E%7B%5Cinfty%7D_%7Bn%3D0%7D%20%28-1%29%5En%20%5C%20%5Cdfrac%7Bx%5E%7B2n%7D%20%7D%7Bx%21%7D%20%3D%201%20-x%5E2%2B%20%5Cdfrac%7Bx%5E4%7D%7B2%21%7D%20%20-%5Cdfrac%7Bx%5E6%7D%7B3%21%7D%2B...%20%5C%20%5C%20%5C%20%20%282%29%7D)
From equation(1), substituting x with (4x), Then:
![\mathtt{cos (4x) = 1 - \dfrac{(4x)^2}{2!}+ \dfrac{(4x)^4}{4!}- \dfrac{(4x)^6}{6!}+...}](https://tex.z-dn.net/?f=%5Cmathtt%7Bcos%20%284x%29%20%3D%201%20-%20%5Cdfrac%7B%284x%29%5E2%7D%7B2%21%7D%2B%20%5Cdfrac%7B%284x%29%5E4%7D%7B4%21%7D-%20%5Cdfrac%7B%284x%29%5E6%7D%7B6%21%7D%2B...%7D)
The first three terms of cos (4x) is:
![\mathtt{cos (4x) = 1 - \dfrac{(4x)^2}{2!}+ \dfrac{(4x)^4}{4!}-...}](https://tex.z-dn.net/?f=%5Cmathtt%7Bcos%20%284x%29%20%3D%201%20-%20%5Cdfrac%7B%284x%29%5E2%7D%7B2%21%7D%2B%20%5Cdfrac%7B%284x%29%5E4%7D%7B4%21%7D-...%7D)
![\mathtt{cos (4x) = 1 - \dfrac{16x^2}{2}+ \dfrac{256x^4}{24}-...}](https://tex.z-dn.net/?f=%5Cmathtt%7Bcos%20%284x%29%20%3D%201%20-%20%5Cdfrac%7B16x%5E2%7D%7B2%7D%2B%20%5Cdfrac%7B256x%5E4%7D%7B24%7D-...%7D)
![\mathtt{cos (4x) = 1 - 8x^2+ \dfrac{32x^4}{3}-... \ \ \ (3)}](https://tex.z-dn.net/?f=%5Cmathtt%7Bcos%20%284x%29%20%3D%201%20-%208x%5E2%2B%20%5Cdfrac%7B32x%5E4%7D%7B3%7D-...%20%5C%20%5C%20%5C%20%283%29%7D)
Multiplying equation (2) with (3); we have :
![\mathtt{ e^{-x^2} cos (4x) = ( 1- x^2 + \dfrac{x^4}{2!} ) \times ( 1 - 8x^2 + \dfrac{32 \ x^4}{3} ) }](https://tex.z-dn.net/?f=%5Cmathtt%7B%20e%5E%7B-x%5E2%7D%20cos%20%284x%29%20%3D%20%28%201-%20x%5E2%20%2B%20%5Cdfrac%7Bx%5E4%7D%7B2%21%7D%20%29%20%5Ctimes%20%28%201%20-%208x%5E2%20%2B%20%5Cdfrac%7B32%20%5C%20x%5E4%7D%7B3%7D%20%29%20%7D)
![\mathtt{ e^{-x^2} cos (4x) = ( 1+ (-8-1)x^2 + (\dfrac{32}{3} + \dfrac{1}{2}+8)x^4 + ...) }](https://tex.z-dn.net/?f=%5Cmathtt%7B%20e%5E%7B-x%5E2%7D%20cos%20%284x%29%20%3D%20%28%201%2B%20%28-8-1%29x%5E2%20%2B%20%28%5Cdfrac%7B32%7D%7B3%7D%20%2B%20%5Cdfrac%7B1%7D%7B2%7D%2B8%29x%5E4%20%2B%20...%29%20%7D)
![\mathtt{ e^{-x^2} cos (4x) = ( 1 -9x^2 + (\dfrac{64+3+48}{6})x^4+ ...) }](https://tex.z-dn.net/?f=%5Cmathtt%7B%20e%5E%7B-x%5E2%7D%20cos%20%284x%29%20%3D%20%28%201%20-9x%5E2%20%2B%20%28%5Cdfrac%7B64%2B3%2B48%7D%7B6%7D%29x%5E4%2B%20...%29%20%7D)
![\mathtt{ e^{-x^2} cos (4x) = ( 1 -9x^2 + \dfrac{115}{6}x^4+ ...) }](https://tex.z-dn.net/?f=%5Cmathtt%7B%20e%5E%7B-x%5E2%7D%20cos%20%284x%29%20%3D%20%28%201%20-9x%5E2%20%2B%20%5Cdfrac%7B115%7D%7B6%7Dx%5E4%2B%20...%29%20%7D)
Finally , multiplying 5 with
; we have:
The first three nonzero terms in the Maclaurin series is
![\mathbf{ 5e^{-x^2} cos (4x) }= \mathbf{ 5 ( 1 -9x^2 + \dfrac{115}{6}x^4+ ...) }](https://tex.z-dn.net/?f=%5Cmathbf%7B%205e%5E%7B-x%5E2%7D%20cos%20%284x%29%20%20%7D%3D%20%5Cmathbf%7B%205%20%28%201%20-9x%5E2%20%2B%20%5Cdfrac%7B115%7D%7B6%7Dx%5E4%2B%20...%29%20%7D)
2 apples. Because you ate one already and you eat another one that equals 2